Synthesis and Crystal Structure of a Tetaraazamacrocyclic Compound - Bi, Jian-Hong; Bi, Wen-Tao; Huang, Zi-Xian; Hu, Nai-Liang (Asian Journal of Chemistry, 2010)
The tetaraazamacrocyclic compound of iron, {L·[Fe(CN)5NO]} (L = 5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradeca-4,11-diene) has been synthesized and determined by X-ray diffraction. The crystal is triclinic, space group P-1 with unit cell parameters: a = 8.167(3) Å, b = 9.345(2) Å, c = 9.702(3)A, α = 63.823(12)º, β = 73.863(14)º, γ = 73.877 (14)º, V = 627.9(3)Å3, Z = 1, Mr = 496.42, Dc = 1.313 Mg/m3, μ = 0.634 mm-1, F(000) = 262, T = 293(2) K, R = 0.0790, wR = 0.1513 for 4885 reflections with I > 2σ(I).